Decorative herbaceous plants in Ukraine (place of cultivation, structure, ornamentality) - Сиплива, Н. О.; Гненна, М. О.; Коляденко, С. С.; Павленко, О. В. (Scientific Progress & Innovations, 2016)
We analyzed quantitative and qualitative composition of the decorative herbaceous plants listed in the State Register of plant varieties which are suitable for dissemination in Ukraine. We reviewed and generalized the results of the cultivation of decorative herbaceous plants of Botanical gardens of Ukraine. Taxonomic, geographical analyses of decorative herbaceous plants are conducted and the rate of assessment of their decorativeness is determined. The varieties of decorative herbaceous plants, which belong to the group of plants with high ornamentality are described.